2021
DOI: 10.32607/actanaturae.11209
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in the Myelodysplastic Syndrome

Abstract: The myelodysplastic syndrome (MDS) holds a special place among blood cancers, as it represents a whole spectrum of hematological disorders with impaired differentiation of hematopoietic precursors, bone marrow dysplasia, genetic instability and is noted for an increased risk of acute myeloid leukemia. Both genetic and epigenetic factors, including microRNAs (miRNAs), are involved in MDS development. MicroRNAs are short non-coding RNAs that are important regulators of normal hematopoiesis, and abnormal changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 111 publications
(110 reference statements)
0
13
0
Order By: Relevance
“…Unlike miRNAs, for which there is a large body of information regarding their role in MDS and has been comprehensively reviewed elsewhere (145,146), information on the role of other types of sncRNAs remain limited. In terms of piRNA expression in MDS, only preliminary data have been reported to date (147,148).…”
Section: Pirnas In Leukemia and Mdsmentioning
confidence: 99%
“…Unlike miRNAs, for which there is a large body of information regarding their role in MDS and has been comprehensively reviewed elsewhere (145,146), information on the role of other types of sncRNAs remain limited. In terms of piRNA expression in MDS, only preliminary data have been reported to date (147,148).…”
Section: Pirnas In Leukemia and Mdsmentioning
confidence: 99%
“…In silico models also identified that onco-miRNAs and miRNAs linked to cell cycle control and death, immune system, angiogenesis, and hematopoiesis are capable of regulating TLN1 expression. Some of those miRNAs, such as miR-17-3p and miR-17-5p, are upregulated in the BM of patients with MDS-RS, refractory cytopenia with multilineage dysplasia (RCMD), and RCMD with ringed sideroblasts, according to a recent review ( 69 ) and other studies ( 70 72 ). Other miRNAs, such as miR-27a-3p and miR-16-5p, were reduced in the plasma of patients with refractory cytopenia with unilineage dysplasia, refractory anemia with ringed sideroblasts, RCMD, MDS-EB1, and MDS-EB2.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to TLN1 , the expression of CEP55 is potentially regulated by oncogenes and miRNAs linked to DNA damage response, cell cycle, and AKT pathway. Several genes that define normal blood cells are regulated by miRNAs, and MDS prognosis is linked to certain miRNAs of the bone marrow, peripheral blood, and mononuclear cells ( 69 ). In fact, some CEP55 -controlling miRNAs identified in our in silico model have been listed as differentially expressed in other patients with MDS ( 70 , 71 , 81 , 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs were selected based on literature data. Experimental analysis involved 17 miRNAs: miR-16-5p, -155-5p, -124-3p, -221-3p, -181a-5p, -15a-5p, -30a-5p, -182-5p, -7-5p, -196b-5p, -20a-5p, -23b-3p, -26a-5p, -29b-3p, -10b-5p, -145-5p, and let-7a-5p [11,[18][19][20][21][22]. The reference miRNA was the geometric mean of Ct values of three reference miRNAs: miR-378-3p, -191-5p, and -103a-3p, which were selected based on our original data and literature data [23].…”
Section: Selection Of Mirnasmentioning
confidence: 99%
“…Both genetic and epigenetic regulatory mechanisms, including microRNAs (miRNAs), are involved in tumor progression of malignant lymphomas with impairment of normal hematopoiesis. MiRNAs are short non-coding RNAs, and their aberrant expression can promote the development of hematological tumors [11]. To date, a number of studies have been published, which analyze levels of miRNA expression in lymph node tissue in NHL [12][13][14].…”
Section: Introductionmentioning
confidence: 99%